The Social Progress Protocol of the ETUC: A suggestion for its future development - Martin Höpner (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2017)
The Social Progress Protocol is a proposal formulated by the European Trade Union Confederation (ETUC). It is a response to judicial decisions of the European Court of Justice on the relationship between fundamental freedoms and collective social rights. The proposal essentially demands a supplementing of European primary law in a way that gives precedence to fundamental social rights in the event of a conflict of laws. This paper underscores the justification of the goals pursued by the Social Progress Protocol and makes suggestions on how it can be developed further. The suggestion consists of two parts. The first part suggests that it is the ambit of European fundamental freedoms that should be focused on rather than the general prioritizing of collective social rights. The second part recommends that the proposal for an activation of European legislation in matters involving collective bargaining rights be dispensed with.
Keywords: 330